Identifying the Wage Differential in the Temporary Employment Services Sector: Evidence for South Africa using Administrative Tax Records. - Cassim, Aalia; Casale, Daniela (Journal of Development Studies, 2022)
Although the temporary employment services (TES) or labour broker sector has been growing in recent decades, and there has been much heated public debate on whether the jobs offered constitute 'decent work', there has been little empirical research on this sector in developing countries. In this paper, we use a unique administrative panel dataset based on income tax records for the period 2011–2015 in South Africa, to explore the wage and benefits differentials between TES and non-TES workers. We find a substantial gross wage differential of around 88 per cent, which remains high at 34 per cent even after accounting for worker fixed effects and controlling for the individual and job characteristics available in the data. We also show that TES workers are much less likely to report benefit contributions than non-TES workers, and when they do, their contributions as a percentage of the gross wage are on average much lower than among non-TES workers. These results add substance to the arguments that TES workers are in a more precarious position than non-TES workers, and that this form of employment contributes to high levels of labour market inequality in South Africa.